(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
Pampatheriidae (Middle Miocene-late Pleistocene) constitutes an extinct clade of Cingulata widely dispersed in South America, entering in Central and North America during the Great American Biotic Interchange. In the Pleistocene of South America, two genera are recorded: Pampatherium (with three species) and Holmesina (with six species). In the Pleistocene palaeofauna of Tarija Valley (Bolivia) one of the most conspicuous recorded taxa are the Cingulata, including Pampatheriidae. Until this contribution, all the remains were classified as P. typum and Pampatherium sp. Here we present a modern taxonomic revision of the Pampatheriidae of the Tarija Valley, based on previous collected and published material together with new materials obtained from fieldwork carried out during 2011-2013. The evidence indicates that a single species of Pampatheriidae is present in the Tarija Valley ( Pampatherium humboldtii ), whereas the presence of P. typum in discarded. From a chrono-stratigraphic point of view, the biochron of this species is restricted to the late Pleistocene. This supports previous hypothesis on the age of the sediments of Tarija Valley (Tolomosa Formation).